Social Media Marketing On Brand Equity Of L’sima Tourism, Intermediating Role : Electronic Word Of Mouth - Mickhael Kurnianto; Titis Shinta Dhewi (Profesional Muda Cendekia Publishing, 2022)
Business promotions are directly affected by current technological advancements. Company operators, particularly those in the tourism industry, may conveniently promote their businesses over the internet nowadays. Therefore, the goal of this research is to figure out the direct and indirect effects of Social Media Marketing on Brand Equity through Electronic Word of Mouth. This study employs a quantitative method with a descriptive explanatory approach. The instrument used is a closed questionnaire distributed to L'Sima's line of business, namely Jagongan Jail. The findings of the study reveal that social media marketing has a significant impact on brand equity through electronic word of mouth at L'Sima assimilation and educational facilities. Based on the empirical findings, the author suggests promotion through Youtube, Instagram, and Facebook. While using the platform, L'Sima's may become more well-known as a tourist destination. Promotions will spread rapidly after the advertising program has been running for a while. The value obtained for the social media marketing variable on brand equity through electronic word of mouth is 0.393, implying that social media promotion has an effect on enhancing the brand equity of L'Sima